2017
DOI: 10.18800/educacion.201701.007
|View full text |Cite
|
Sign up to set email alerts
|

Narrativas sobre a inclusão de uma criança autista: desafios à prática docente

Abstract: ResumoO autismo é tema amplamente explorado na literatura. Apesar disso, a inclusão escolar da criança autista ainda se constitui um desafio. Partindo deste pressuposto, o objetivo da pesquisa foi identificar quais os desafios da prática docente no acompanhamento de uma criança autista e em que condições a sua inclusão ocorreu. A pesquisa qualitativa, de natureza descritiva e exploratória foi realizada nos meses de agosto a outubro de 2014 em uma instituição privada de Brasília. Em síntese, o estudo leva, por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
1
0
0
7
Order By: Relevance
“…Regarding the gap between public policies and their operationalization, data agree with the results of studies by Chahini and Souza (2016), Luz, Gomes and Lira (2017), Ferreira (2017), Aguiar and Pondé (2017) and Cabral and Marin (2017), in which the authors identified barriers in the inclusion context and emphasized the need to overcome these obstacles so that Inclusive Education becomes a reality. Participants who responded that there were no barriers to inclusion in Early Childhood Education said so based on their personal experiences, without entering into the specifics of how public policies have or have not been applied to Early Childhood Education, as observed in the following statements: "We never had.…”
Section: Resultssupporting
confidence: 87%
“…Regarding the gap between public policies and their operationalization, data agree with the results of studies by Chahini and Souza (2016), Luz, Gomes and Lira (2017), Ferreira (2017), Aguiar and Pondé (2017) and Cabral and Marin (2017), in which the authors identified barriers in the inclusion context and emphasized the need to overcome these obstacles so that Inclusive Education becomes a reality. Participants who responded that there were no barriers to inclusion in Early Childhood Education said so based on their personal experiences, without entering into the specifics of how public policies have or have not been applied to Early Childhood Education, as observed in the following statements: "We never had.…”
Section: Resultssupporting
confidence: 87%
“…A respeito dos termos laudo e diagnóstico, observamos que 8 dos 13 artigos referem-se a laudo e todos os 13 falam de diagnóstico. Sobre laudo: 2 artigos esclarecem a não obrigatoriedade deste documento para as práticas educacionais inclusivas (Christmann & Pavão, 2018;Bridi & Meireles, 2014); 2 artigos usam o termo laudo para se referir ao aluno em situação de inclusão (Franco & Neres, 2017;Scherer & Dal'igna, 2015); 2 artigos usam o termo laudo para falar do quadro diagnóstico dos estudantes que participaram das pesquisas (Silva et al, 2019;Luz et al, 2017); 1 artigo faz referência à situação em que o laudo aparece como condição para a matrícula escolar (Tada et al, 2012); e 1 artigo relata situação em que a criança do estudo de caso recebeu laudo psicológico lhe encaminhando para Programa de Apoio à Educação Especial.…”
Section: Resultsunclassified
“…A análise de síntese dos 13 artigos foi realizada por mais dois autores, com isso, quatro autores fizeram a extração das informações, as quais apresentamos nas seções seguintes. (Christmann & Pavão, 2018;Bridi & Meirelles, 2014;Tada, Lima, Melo & Correio, 2012;Silva et al, 2019;Luz, Gomes & Lira, 2017;Heredero, 2010;Leite & Silva, 2012) não explicitaram nenhuma moldura teórico-epistemológica.…”
Section: Métodounclassified
See 2 more Smart Citations